PENGARUH PROFITABILITAS, KOMISARIS INDEPENDEN, CAPITAL INTENSITY DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Izdahara Afrina; Dirvi Surya Abbas; Imam Hidayat; Ahmad Zaki Mubbarok (Akuntansi, 2022)
Tax aggressiveness is an action that aims to reduce profits taxable through tax planning using either inclusive or does not include tax evasion. Company strategythat is not in line with expectations society and this tax aggressiveness act is detrimental to the government because the government cannot optimize tax revenue. The population of this study includes all manufacturing companies in the pharmaceutical sub- sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 8 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results show that: (1) profitability has no effect on tax aggressiveness, (2) independent commissioners have no effect on tax aggressiveness (3) capital intensity has a positive effect on tax aggressiveness (4) leverage have no effect on tax aggressiveness.